From Keynes to Piketty The Century that Shook Up Economics - de Haan, Peter; SpringerLink (Online service) (London : Palgrave Macmillan UK (Imprint), 2016)
From Keynes to Piketty provides the reader with an accessible and entertaining insight into the development of economic thought over the past century. Starting with John Maynard Keynes's bestseller, The Economic Consequences of Peace (1919), and ending with Thomas Piketty's blockbuster, Capital in the Twenty First Century (2014), the author explains which dramatic political and economic events changed the way economists interpreted these events, and how they revolutionized the economic science. The book contains biographies of Keynes, Schumpeter, Galbraith, Hayek, Friedman, Hirschman, North, and Piketty, alongside others, and highlights their extraordinary lives and works, anecdotes about them, and their often sharp differences of opinion. Extensive summaries of their main works provide the interested scholar and student with an accurate presentation of their contents. A must-read for all those who wonder what happened to economics during the past century, and why.
1. Political and Economic Developments 1914-2014 -- 2. The Great War and The Great Depression -- 3. Capitalism or Socialism; that's the question -- 4. Affluence -- 5. The Return of Neoclassical Economics -- 6. Capitalism Riding High -- 7. The Great Recession -- 8. Inequality Revisited -- Epilogue.
Keywords: Economic history; History of Economic Thought/Methodology.